2017
DOI: 10.1186/s13099-017-0169-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, virulence potential, and pulsed-field gel electrophoresis profiling of Shiga toxin-producing Escherichia coli strains from cattle

Abstract: BackgroundAs a primary source of Shiga-toxin-producing Escherichia coli (STEC) infection, cattle are often targeted to develop strategies for reducing STEC contamination. Monitoring the virulence potentials of STEC isolates from cattle is important for tracing contamination sources, managing outbreaks or sporadic cases, and reducing the risks for human infection. This study aimed to investigate the prevalence of STEC in cattle farm samples in South Korea and to assess their virulence potentials.ResultsIn total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 66 publications
4
22
2
Order By: Relevance
“…The prevalence of infected cattle per farm ranged from 2.9% to 43.3% consistent with reports from Japan and the United Kingdom which reported similar ranges (Ellis‐Iversen et al, ; Gunn et al, ; Lee, 2017). However, the farms prevalence rates obtained in this study were relatively lower in comparison to studies in Brazil, South Korea and USA cattle farms which reported up to 100% for cattle that tested positive for STEC (Cull et al, ; Dong et al, ; Pereira, Brod, Rodrigues, Carvalhal, & Aleixo, ). We also observed that particular serotypes were confined to specific farms.…”
Section: Discussioncontrasting
confidence: 86%
“…The prevalence of infected cattle per farm ranged from 2.9% to 43.3% consistent with reports from Japan and the United Kingdom which reported similar ranges (Ellis‐Iversen et al, ; Gunn et al, ; Lee, 2017). However, the farms prevalence rates obtained in this study were relatively lower in comparison to studies in Brazil, South Korea and USA cattle farms which reported up to 100% for cattle that tested positive for STEC (Cull et al, ; Dong et al, ; Pereira, Brod, Rodrigues, Carvalhal, & Aleixo, ). We also observed that particular serotypes were confined to specific farms.…”
Section: Discussioncontrasting
confidence: 86%
“…Anvarinejad et al reported 9 to 16 DNA bands with molecular size of 2 to 660kbp in molecular typing of E. coli isolates from patients with cyctitis and pyelonephritis [ 57 ]. Dong et al reported 15–20 distinct bands in genotyping of Shiga toxin produced by E. coli isolates [ 41 ]. Ejrnaes et al reported 15–20 bands with 50kbp to 1200kbp molecular sizes by typing UPEC strains [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PFGE profiles were compared using In silico stimulation of molecular experiment with a dice similarity coefficient and UPGMA analysis to create the dendrogram. To analyze genetic relatedness, cut off line at 85% was considered [ 38 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…The persistence and ability of ETEC to survive in effluents like cattle effluent are mostly unknown. However, ETEC could survive for up to three months in freshwater [ 43 ] and was able to form biofilms in a wet environment [ 44 ].…”
Section: Discussionmentioning
confidence: 99%